Discourse communication strategies used by the deaf community: a case study of Nzeve deaf children’s centre, zimbabwe. - Mudefi, Clara Tatenda (Midlands State University, 2017)
The thrust of the study is to investigate and examine the CS that are employed by the Deaf Community in solving communication challenges with the hearing people. It is important to note that although the hearing and the hearing impaired people seem to be living in the same world, they transform in two separate discourse communities as there is a language barrier. Communication is an important tool in our day to day lives therefore has to be exercised efficiently for unity sake. CS play a vital role in achieving communication where there are challenges. The research was based on the qualitative research methodology, with interviews and questionnaires as research instruments. A random sampling technique identified the respondents who attended activities at the Nzeve Deaf Children’s Centre, an organisation that was used as the case study. Findings were that, CS that are used by the deaf people are to a larger extend efficient though loopholes still portray mainly due to the language difference. The Centre has assisted the deaf people to overcome stereotypes of disability, in that it is not inability, by the programmes it offers. The researcher gave recommendations at the end of the last chapter that in order to overcome this communication challenge, sign language tutorials and deaf awareness are to be exercised in creating a bridge for the barrier